Prevalence of talon cusp: Systematic literature review, meta-analysis and new scoring system. (May 2021) - Decaup, Pierre-Hadrien; Garot, Elsa; Rouas, Patrick
Highlights: Talon cusp is a developmental anomaly with many patterns. Talon cusp occurs in approximately 1, 67 % of the population. Talon cusp and sex are non-statically associated. New 3D classification should improve talon cusp clinical and evolutionary implication. Abstract: Objectives: Talon cusp is a developmental anomaly consisting of a vertical ridge or cusp projecting labially or lingually from an anterior permanent or primary tooth. A range of prevalence between 0.06 % and 40.8 % has been reported in the literature. Although many epidemiological studies have been conducted, no synthesis of these data has been performed to date. The aim of this paper was to determine the prevalence of talon cusp and to investigate the link between sex and talon cusp. Source: A systematic search was undertaken using the PubMed/Medline, Embase and Cochrane Library electronic databases for publications from 1981 to 2020 investigating the prevalence of talon cusp and the link between talon cusp and sex. Study selection: Three reviewers selected the studies independently, extracted the data in accordance with the PRISMA statement, and assessed the risk of bias via the GRADE & Cochrane approaches. Results: From 39 potentially eligible studies, 9 were selected for full text analysis and 8 were included in the meta-analysis, representing 35, 224 participants. The meta-analyses were performed with a random model, calculating a weighted-mean prevalence (at least one talon cusp per individual) of 1.67 %. Sex and talon cusp were not statistically significantly associated in our study (OR = 1.10; 95 % CI [0.82–1.47]; p > 0.05). Discussion: We report the first prevalence of talon cusp provided by meta-analysis in a non-syndromic sample. A non-statistically significant association between sex and talon cusp is relevant in terms of genetic etiology. In order to improve the homogeneity and accuracy of the results of further studies, we propose a new universal scoring system for talon cusp. Clinical significance: Talon cusp is a developmental anomaly with various clinical implications. Therapeutics may vary from simple monitoring to extraction of the supporting tooth. This condition occurs in approximately 1.67 % of the population.